Seasonal variations in the phytoplankton community in a lentic ecosystem and its relationship to environmental variables (An applied study in the artificial lake of the island of Baghdad, Iraq) - Hind Mahdi Salih Al-Saeedi; Ibrahim M. A. Al-Salman (Zien Journals, 2022)
The current study was applied to a lentic aquatic ecosystem for the period from October 2021 to June 2022 in two sites within the lake of the tourist island of Baghdad, in addition to a control site representing the source of the lake's water and a dilution site representing the area of water exit from the lake and mixing with river water, and included the measurement of twelve physicochemical factors of the water of the lake environment and the sites of control and dilution and the identification of its qualitative and quantitative effect on the community of phytoplankton within the study area, in addition to the application of a number of evidence Biotechnology for Water Quality Assessment. The results showed the variation in the intensity of the average values of the physicochemical factors of the lake water affected by climatic variations and human activities between the seasons of the year and the study sites, with air and water temperatures recording averages of 23.78 °C and 17.75 °C respectively, and while turbidity recorded a high average value of 8.25 NTU, total dissolved solid recorded 440.5 mg/L. As for electrical conductivity, it indicated a surplus in the autumn and summer seasons, the general average reached dangerous limits of 958.7 close to the maximum allowable limit, while the pH recorded an average of 8.02, the average dissolved oxygen recorded 7.26 mg/L, and the Biodemand of oxygen was 3.03 mg/L. Nitrates, phosphates, sulphates and silica also averaged 2.07, 0.22, 252.6 and 3.06 mg/L respectively. While the qualitative study of Phytoplankton concluded that 107 species belonging to 43 genera were recorded at the four sites with 70 species belonging to 32 genera within the lake, and the diagnosed genera and their species were organized based on the sites and the seasons in which they appeared, and these genera belonged to eight species, seven of which appeared in the two lentic sites: Chlorohyceae, Bacillariophyceae, Cyanophyceae, Cryptophyceae, Dinophyceae, Chrysophyceae, Xanthophyceae and Euglenophyceae.
Keywords: Bacillariophyceae; Cyanophyceae; Dinophyceae; Xanthophyceae